Comparison of U.S. and Japanese Consumers' Perceptions of Remanufactured Auto Parts. (24th August 2016) - Matsumoto, Mitsutaka; Chinen, Kenichiro; Endo, Hideki
Summary: This study compares U.S. and Japanese consumers' perceptions of remanufactured auto parts. Remanufactured parts have a long history and enjoy continuing success in the U.S. domestic aftermarket. In contrast, although Japan's domestic aftermarket is growing, it remains comparatively underdeveloped. This research examines whether customers' perceptions of remanufactured products explain their lower acceptance in Japan. Our Internet survey of 440 U.S. and 300 Japanese respondents examined their knowledge of remanufactured auto parts, perceptions of their benefits and risks, and price consciousness. The results reveal that Japanese consumers know less about remanufactured products, perceiving them as entailing lower benefits and greater risk, especially concerning quality, and are less price conscious. Drawing on its results, this study suggests measures to promote markets for remanufactured auto parts in Japan and in economies in which such markets are in an early stage of development.